A Comparative Study of Anodic Oxidation and Electrocoagulation for Treating Cattle Slaughterhouse Wastewater - Salazar-Gonzalez, R; Garcia-Mena, V; Sandoval, A; Sandoval, A (Elsevier Ltd, 2022)
In this study, industrial cattle slaughterhouse wastewater (ICSHWW) was treated by anodic oxidation (AO) and electrocoagulation (EC) processes using different electrode materials. Total organic carbon (TOC), chemical oxygen demand (COD), and total phosphorus (TP), among other parameters, were analyzed during the treatments. Electrochemical techniques were carried out in batch operation mode during five hours applying different current densities in sulfate and chloride media. The industrial cattle slaughterhouse wastewater contained TOC 1150 mg L-1, COD 4320 mg L-1, TP 25 mg L-1, TN 76 mg L-1, turbidity 516 NTU, color -absorbance 0.36 A.U. at 416 nm-, conductivity 2.79 mS cm-1, and pH 7.18. The highest TOC removal efficiencies were found at j = 20 mA cm-2 using the EC process (> 88%), with an energy consumption around 0.01 kW h m-3. Moreover, a complete discoloration and disinfection were achieved. Considering the high consumption of the freshwater destined to the livestock sector and global scarcity of water, electrochemical processes are an effective tool for decontaminating industrial waters produced from the meat industry. © 2022 Elsevier Ltd.